Penggunaan Buku Anak Hebat untuk Meningkatkan Kemampuan Menulis Matematika Peserta Didik Berkebutuhan Khusus di Tk Sari Asih Ii Yogyakarta - Nurjannah, Siti; Hilma Rahmatillah (Business Finance Analyst Co., 2025)
Writing is a foundational skill essential for early childhood academic success, yet children with learning difficulties such as dysgraphia often struggle with basic handwriting, including mathematical symbol writing. This study aimed to explore the effectiveness of the Buku Anak Hebat (Great Children’s Book) as an intervention tool to improve number awareness and mathematical writing skills in a kindergarten student with special needs at TK Sari Asih II Yogyakarta. Using a qualitative case study design, the research involved one purposively selected student and was conducted in three phases: initial assessments of visual perception, motor coordination, and basic mathematical skills; followed by two stages of intervention using the Buku Anak Hebat; and systematic evaluation of student performance. The findings showed marked improvements in the student’s ability to write numbers independently, reduced reliance on assistance, and increased confidence and motivation. The intervention successfully stimulated sensory-motor integration and supported procedural memory development through repetitive and engaging visual-kinesthetic activities. These outcomes suggest that consistent, well-structured, and emotionally supportive media can significantly improve foundational writing skills in children with writing difficulties. The study concludes that early, tailored interventions using interactive learning materials can enhance both mechanical and cognitive aspects of mathematical writing in inclusive educational settings.